2021
DOI: 10.1021/acsenergylett.1c01624
|View full text |Cite
|
Sign up to set email alerts
|

Water or Anion? Uncovering the Zn2+ Solvation Environment in Mixed Zn(TFSI)2 and LiTFSI Water-in-Salt Electrolytes

Abstract: Applications of aqueous zinc batteries for grid-scale energy storage are limited by their poor reversibility and the competing water splitting reaction. The recent invention of a water-in-salt (WIS) electrolyte concept provides a new route enabling a stable and highly reversible aqueous zinc battery chemistry. In the present work, a mixed zinc bis(trifluoromethane sulfonyl)imide (Zn(TFSI) 2 ) and LiTFSI WIS electrolyte was studied using X-ray total scattering, X-ray absorption, and Fourier transform infrared s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 32 publications
(49 reference statements)
4
39
0
Order By: Relevance
“…In addition, the calculated RDFs and residence times suggested that the interactions with the second solvation shells are quite strong for both Cu 2+ and Cu + ions. Similar behavior has been reported previously for divalent metal ions such as Zn 2+ , but not observed for monovalent ions such as Li + …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, the calculated RDFs and residence times suggested that the interactions with the second solvation shells are quite strong for both Cu 2+ and Cu + ions. Similar behavior has been reported previously for divalent metal ions such as Zn 2+ , but not observed for monovalent ions such as Li + …”
Section: Discussionsupporting
confidence: 90%
“…Strong interactions between metal ions and the solvation species beyond the first solvation shell in electrolytes have been reported. 40,41 The well-defined peaks at ∼5 Å in Cu−Cl RDFs in Figure 4 indicate that such strong interactions may exist between the second solvation shell for both Cu 2+ and Cu + cations in these electrolyte mixtures. To confirm this, the dynamics of the Cu−Cl and Cu−O(EG) interactions were studied in terms of the following correlation function 42…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…Thus, optimizing the solvated structure of Zn 2+ ions and decreasing the content of free H 2 O is a simple and effective way to eliminate dendrite growth, parasitic reactions and the dissolution of cathode materials. [17][18][19][20][21][22][23][24][25] Recently, some scientic researchers reported that both highly concentrated organic salts and solvent additives with strong solvating capability could coordinate with Zn 2+ ions to form close ion pairs instead of [Zn(H 2 O) 6 ] 2+ ions, signicantly inhibiting the activity of H 2 O in the electrolyte. [26][27][28][29][30][31][32] Nitriles, a group of non-ionic and highly polar plasticcrystalline neutral molecules, are usually used in industrial Zn electroplating, as plasticizers for polymer electrolytes, and as additives or solvents for liquid electrolytes.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, optimizing the solvated structure of Zn 2+ ions and decreasing the content of free H 2 O is a simple and effective way to eliminate dendrite growth, parasitic reactions and the dissolution of cathode materials. 17–25 Recently, some scientific researchers reported that both highly concentrated organic salts and solvent additives with strong solvating capability could coordinate with Zn 2+ ions to form close ion pairs instead of [Zn(H 2 O) 6 ] 2+ ions, significantly inhibiting the activity of H 2 O in the electrolyte. 26–32…”
Section: Introductionmentioning
confidence: 99%
“…Even though they could not report the diffusion coefficient from QENS measurement at 20:1 concentration because of the limitations of the spectrometer, they have reported the diffusion coefficients of acetonitrile at 5:1 and 2:1 concentration at 275 K, which showed a 10-fold decrease in the diffusivity due to the reduction of the size of the solvation shell and an increase in the number of Li ions as a function of concentration, which influence more of the solvent molecules. Not only in the acetonitrile–LiTFSI systems but also in the water–LiTFSI system at low concentration (1 M), Zhang et al observed a small peak at Q < 0.5 Å –1 , suggesting a formation of a larger (∼13 Å) solvation shell around the ions at a lower concentration. For our 1 M solutions, our numerical calculation (see Table ST2 in Supporting Information for detail) also shows the formation of a solvation shell of ∼12 Å around the ions.…”
mentioning
confidence: 99%